Technology-Based Interventions in Schizophrenia Patients : A Narrative Review - Iyus Yosep; Firman Sugiharto; Shopia Puji Lestari; Syifa Fauziah Mutaqin; Linlin Lindayani; Heni Purnama; Rohman Hikmat (STIKep PPNI Jawa Barat, 2022)
Aims: The development of technology to facilitate the management of schizophrenia is still very limited so that many people don’t know the benefits and efficacy of using technology as an intervention in schizophrenia patients. Objective:This literature review aimed to describe and determine the efficacy and benefits of using the technology used in schizophrenia patients. Method: The method used was a narrative review by combining articles from the PubMed, EbscoHost, Taylor and Francis, and Google Shcolar databases. The keywords used were “adults” OR “middle aged” AND “telenursing” OR “telemedicine” OR “telehealth” AND “schizophrenia patient”. Result: From these 6 articles, it was founde that there were several perceived benefits of using technology as an additional intervention, such as medication adherence, involvement in recovery and symptom control, and early detection of cognitive function in schizophrenic patients. Conclusion: Interventions using technology such as telehealth, telenursing, and telemedicine can be supportive interventions for the care of schizophrenic patients, especially to assist recovery or rehabilitation. Nursing Implications: The existence of this study can provide an overview to nurses regarding what technology-based support interventions can be given to schizophrenic patients along with their benefits.